Kinetic, product, and computational studies of the ultrasonic induced degradation of 4-methylcyclohexanemethanol (MCHM). (1st December 2017) - Cui, Danni; Mebel, Alexander M.; Arroyo-Mora, Luis E.; Holness, Howard; Furton, Kenneth G.; O'Shea, Kevin
Abstract: A massive spill of 4-methylcyclohexanemethanol (MCHM), a semi-volatile organic compound, contaminated the Elk river and forced the recent closure of tap water for nearly 300, 000 residents. Typical water treatment methods are not effective for MCHM remediation, however ultrasonic irradiation leads to its rapid pseudo-first order degradation. The degradation processes were effectively modeled employing heterogeneous kinetic models with the reaction surface corresponding to the gas-liquid interface of the cavitation bubble. The Freundlich model which takes into account non-uniform distribution within the reactive zone showed the strongest correlation to the observed degradation kinetic data with R 2  > 0.99. Solute-solute clustering behavior is proposed to explain non-uniform distribution of MCHM. The results indicate the degradation occurs predominantly at the gas-liquid interface as a result of hydroxyl radical reactions and pyrolysis with primary reaction products, (4-methylcyclohexenyl) methanol and 4-methylcyclohexanone. Computational methods using density functional B3YPL/6-311G** calculations with Gaussian 09 provided insight of the hydroxyl radical and pyrolytic degradation pathways for the isomeric and conformational forms of MCHM. Our studies demonstrate that heterogeneous kinetic models and computational methods are important tools for the fundamental understanding and effective application of ultrasonically mediated degradation of MCHM which may be extended to a number of semi-volatile compounds. Graphical abstract: Image 1 Highlights: Effective and rapid degradation of MCHM. Successful modeling of the degradation kinetics using Langmuir-Hinshelwood and Freundlich adsorption models. Elucidation of degradation pathways using product and computational studies.